Pendampingan Sertifikat Halal Pada UMKM di Kecamatan Warungasem Kabupaten Batang - Maula, Intan Athiyatul; Nofitasari, Dian; Adinia, Atinal Husna; Suryaning Putri, Sheylomitha; Mubarok, M. Sultan (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
UMKM are the foundation for the economy in Indonesia, so in running their business, a business permit number (NIB) is certainly needed so that their business is recognized by the government. In addition, halal products are an obligation that must fulfill Islamic law, namely in terms of cleanliness, quality, and safety of the production process must be under a halal quality management system. This is what underlies the author to provide assistance to UMKM business actors in Warungasem sub-district, Batang district. This assistance is carried out because there are still many business actors who do not know and have a business license number (NIB) or halal certificate on their products. This article aims to provide understanding and assistance to business actors related to making NIB. This mentoring method goes through several four stages, namely planning and collecting data on UMKM actors, socializing and collecting data on NIB requirements, registering and making NIB, printing NIB documents. Based on the results of the mentoring activities that have been carried out in Warungasem sub-district, Batang district regarding assistance in making NIB for UMKM actors, it can be concluded that researchers found five UMKM actors who were willing to register their businesses in order to obtain NIB. This activity has succeeded in providing assistance until registration and obtaining an NIB even though initially there were several businesses that could not be registered. With the assistance in making a Business Identification Number (NIB), it is hoped that it can increase awareness and understanding of the importance of halal certification for micro and small and medium enterprises (UMKM).